Post-marketing safety of anakinra and canakinumab: a real-world pharmacovigilance study based on FDA adverse event reporting system - Liu, Hao; Yan, Wei; Li, Jinsong; Yan, Dezhi; Luo, Di (Frontiers in Pharmacology, 2025)
BackgroundAnakinra and canakinumab are two FDA-approved IL-1 blockers indicated for the treatment of multiple autoinflammatory diseases, yet their safety has not been comprehensively analyzed. We aimed to assess the safety signals associated with anakinra and canakinumab by conducting a pharmacovigilance analysis using the FDA Adverse Event Reporting System (FAERS) database.MethodsAdverse reaction data spanning from the first quarter of 2004 to the fourth quarter of 2023 was downloaded from the FAERS database. A disproportionality analysis utilizing various methods, including the reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and Empirical Bayes Geometric Mean (EBGM), was conducted.ResultsAnakinra and canakinumab were identified as the primary suspect drugs for adverse events (AEs) in 7,544 and 8,044 reports, respectively. The most commonly reported SOCs for both drugs were general disorders and administration site conditions. Subgroup analyses indicated that the most commonly reported SOC signals among health professionals and non-health professionals remained consistent across both medications. At the preferred term (PT) level, consistent with the drug labeling, the common AEs for anakinra and canakinumab included injection site reactions (ISRs) and infections. Further analysis revealed a higher frequency of ISRs with anakinra, including injection site pain and erythema. In contrast, canakinumab was associated with more gastrointestinal disorders (abdominal pain, mouth ulceration, and inflammatory bowel disease) and respiratory disorders (cough, oropharyngeal pain, and rhinorrhea); these conditions predominantly occurred among minors. Notably, no significant safety signals related to tuberculosis infection or reactivation were observed, and the frequency of AEs related to hepatic injury and malignancy was low.ConclusionThis study confirms the favorable safety profiles of anakinra and canakinumab, offering critical insights into rational drug usage and safety regulations.